Isolated tibiotarsal dislocation: A case report - Zeddouk Hassan; Boufettal Moncef; Rida-Allah Bassir; Mekkaoui Jalal; Mohammed Reda Fekhaoui (Trauma Case Reports)
Isolated tibio-tarsal dislocations are uncommon as they are associated in most of the cases with fractures resulting from high-energy injuries. We report a case of a 28-year-old pregnant woman patient who suffered a closed posterior tibio-tarsal dislocation after a tree fell on her foot due to strong wind that day. The treatment consisted of a closed bloodless reduction, immobilization, a close follow up and rehabilitation. Six months later, our patient reported no sign of pain or instability and a good range of movement. In this case of an injured pregnant woman, we discuss the treatment and the importance of an early and adequate rehabilitation and also the challenge in radiographic study for a pregnant woman.